First year nursing students' reflections about developing their verbal nursing skills during their nursing education in China: a qualitative study - Xiaoling Zhu; Mikael Rask; Hongbo Xu (Frontiers Media S.A., 2023)
ObjectiveThe aim of the study is to explore the expectations of a group of first-year nursing students in China about developing their verbal and social interactional skills during their nursing education.BackgroundNursing students' communication skills were not fully developed in China. Students have many challenges to face regarding developing their nursing skills, especially interaction skills, when they start their education.DesignA qualitative design was used in this research.MethodTwelve second-semester undergraduate nursing students were interviewed on the basis of purposive sampling, and qualitative content analysis was employed.ResultsThe main theme was 'facilitating a caring nurse-patient relationship' and 'using a knowledge base for performing nursing care'. The first theme comprises two sub-themes, 'caring approach' and 'helping and involving the patient in care', with three and two categories, respectively. The second theme comprises the two sub-themes, 'knowledge needed to be able to understand the patient' and 'health and treatment information', with three and two categories, respectively.ConclusionA synthesis of both knowledge and practice is needed to improve the nursing students' interaction and professional skills during their nursing education.